15-Deoxy-Δ12,14-Prostaglandin J2 Modifies Components of the Proteasome and Inhibits Inflammatory Responses in Human Endothelial Cells - Marcone, Simone; Evans, Paul; Fitzgerald, Desmond J. (Frontiers in Immunology, 2016)
15-Deoxy-delta12,14-prostaglandin J2 (15d-PGJ2) is an electrophilic lipid mediator derived from PGD2 with potent anti-inflammatory effects. These are likely to be due to the covalent modification of cellular proteins, via a reactive α,β-unsaturated carbonyl group in its cyclopentenone ring. This study was carried out to identify novel cellular target(s) for covalent modification by 15d-PGJ2 and to investigate the anti-inflammatory effects of the prostaglandin on endothelial cells. The data presented here show that 15d-PGJ2 modifies and inhibits components of the proteasome and consequently inhibits the activation of the NF-kB pathway in response to TNF-a. This, in turn, inhibits the adhesion and migration of monocytes toward activated endothelial cells, by reducing the expression of adhesion molecules and chemokines in the endothelial cell. The effects are consistent with the covalent modification of 13 proteins in the 19S particle of the proteasome identified by mass spectrometry and the suppression of proteasome function, and were similar to the effects seen with a known proteasome inhibitor (MG132). The ubiquitin-proteasome system has been implicated in the regulation of several inflammatory processes and the observation that 15d-PGJ2 profoundly affects the proteasome functions in human endothelial cell suggests that 15d-PGJ2 may regulate the progression of inflammatory disorders such as atherosclerosis.